Nursing Process Related to the Nursing Focus "Airway Clearance": A Scoping Review - Luís Gaspar; Neuza Reis; Paula Sousa; Abel Paiva e Silva; Alexandrina Cardoso; Alice Brito; Fernanda Bastos; Joana Campos; Paulo Parente; Filipe Pereira; Natália Machado (MDPI AG, 2024)
Background: Airway clearance impairment has a significant impact on self-care and quality of life. Identifying clinical data, nursing diagnoses, and nursing interventions is essential to clinical reasoning and enhancing nursing care. This study aims to map the existing evidence on clinical data, nursing diagnoses, and nursing interventions addressing the nursing focus on "airway clearance". Methods: Research was conducted based on Joanna Briggs's Scoping Review Methodology. We searched four databases for published studies until December 2023. Results: From the initial 1854 studies identified, 123 were included in the review. The findings highlighted two areas of nursing attention: one related to signs and symptom management, and the other related to education and coping strategies. The data that led to nursing diagnoses were divided into cognitive and clinical data. The nursing diagnoses were mostly related to secretion retention, excessive mucus production, and airway obstruction. The most commonly identified nursing interventions were educational interventions assembled into predesigned education programs rather than patient-tailored programs. Conclusions: Findings can add substantial value for systematizing the nursing process related to "airway clearance", improving nursing decision-making and care quality. This study was prospectively registered with the Open Science Framework (OSF) on 02 December 2022, with the registration number wx5ze.